Inhibition in the face of emotion: Characterization of the spatial‐temporal dynamics that facilitate automatic emotion regulation - Taylor, Margot J.; Robertson, Amanda; Keller, Anne E.; Sato, Julie; Urbain, Charline; Pang, Elizabeth W. (Human brain mapping, 2018)
Emotion regulation mediates socio‐cognitive functions and is essential for interactions with others. The capacity to automatically inhibit responses to emotional stimuli is an important aspect of emotion regulation; the underlying neural mechanisms of this ability have been rarely investigated. Forty adults completed a Go/No‐go task during magnetoencephalographic (MEG) recordings, where they responded rapidly to either a blue or purple frame which contained angry or happy faces. Subjects responded to the target color in an inhibition (75% Go trials) and a vigilance condition (25% Go trials). As expected, inhibition processes showed early, sustained activation (200–450 ms) in the right inferior frontal gyrus (IFG). Emotion‐related inhibition processes showed greater activity with angry faces bilaterally in the orbital‐frontal gyri (OFG) starting at 225 ms and temporal poles from 250 ms, with right hemisphere dominance. The presence of happy faces elicited earlier activity in the right OFG. This study demonstrates that the timing of inhibition processes varies with the emotional context and that there is much greater activation in the presence of angry faces. It underscores the importance of the right IFG for inhibition processes, but the OFG in automatic emotion regulation.